2019
DOI: 10.1177/1178223419829072
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Therapy for Breast Cancer as a Model for Translational Research

Abstract: Neoadjuvant therapy, where patients receive systemic therapy before surgical removal of the tumour, can downstage tumours allowing breast-conserving surgery, rather than mastectomy. In addition to its impact on surgery, the neoadjuvant setting offers a valuable opportunity to monitor individual tumour response. The effectiveness of standard and/or potential new therapies can be tested in the neoadjuvant pre-surgical setting. It can potentially help to identify markers differentiating patients that will potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 63 publications
0
52
0
Order By: Relevance
“…Proper staging is critical for determining the appropriate clinical treatment course and surgical planning. Neoadjuvant therapies, where patients receive systemic therapy before surgical removal of the tumor, can downstage tumors allowing breast-conserving surgery, rather than mastectomy [91,95]. The effectiveness of standard and/or potential new therapies can be tested in the neoadjuvant pre-surgical setting [91].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proper staging is critical for determining the appropriate clinical treatment course and surgical planning. Neoadjuvant therapies, where patients receive systemic therapy before surgical removal of the tumor, can downstage tumors allowing breast-conserving surgery, rather than mastectomy [91,95]. The effectiveness of standard and/or potential new therapies can be tested in the neoadjuvant pre-surgical setting [91].…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of standard and/or potential new therapies can be tested in the neoadjuvant pre-surgical setting [91]. It can potentially help to identify markers differentiating patients that will potentially benefit from continuing with the same or a different adjuvant treatment enabling personalised treatment [95].…”
Section: Discussionmentioning
confidence: 99%
“…e varying roles of the different regimens used as neoadjuvant chemotherapy need to be investigated, as it is currently unclear which treatment regimen suits best [14]. Prior to the surgical removal of the tumors, patients receive neoadjuvant chemotherapy and can downstage tumors allowing breast-conserving surgery, rather than mastectomy and setting offers a valuable opportunity to monitor individual tumor response [15]. Prior to the surgical removal of the tumors, patients receive neoadjuvant chemotherapy, can downstage tumors allowing breast-conserving surgery, rather than mastectomy and setting which offers a valuable opportunity to monitor individual tumor response [15].…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the surgical removal of the tumors, patients receive neoadjuvant chemotherapy and can downstage tumors allowing breast-conserving surgery, rather than mastectomy and setting offers a valuable opportunity to monitor individual tumor response [15]. Prior to the surgical removal of the tumors, patients receive neoadjuvant chemotherapy, can downstage tumors allowing breast-conserving surgery, rather than mastectomy and setting which offers a valuable opportunity to monitor individual tumor response [15]. In 42 patients who received neoadjuvant chemotherapy, the expression level of COL4A1 in the tumor, as assessed by immunohistochemistry, was not associated with age (Table 2), but was highly positively correlated with stage status (P � 0.046).…”
Section: Discussionmentioning
confidence: 99%
“…Neoadjuvant chemotherapy (NAC) also provides a powerful research opportunity since matched primary tumour samples from before (diagnostic biopsies) and after therapy (resections) may be available. With respect to chemotherapy response, a relevant hypothesis is that tumour cells that remain post-NAC have characteristics associated with therapy resistance, while characteristics lost from tumour cells in the matched pre-NAC sample are associated with sensitivity; therefore, comparative analysis of these matched samples can give insights into both resistance and sensitivity (11). Based on this hypothesis, investigators have examined expression pre-NAC and post-NAC and identified individual molecules such as bFGF (12), families of molecules such as xenobiotic drug pumps (13), or pathway-level gene expression changes (14) that were associated with relative resistance.…”
Section: Introductionmentioning
confidence: 99%